KAJIAN FISIKOKIMIA EDIBLE CASING SOSIS BERBASIS GELATIN CEKER AYAM - La Choviya Hawa; Utami Yolanda BR Ginting; Bambang Susilo; Laras Putri Wigati (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
Plastic films are material that commonly used as preservative material for food products such as sausages, at first it aims to preserve the products from the environment and to maintain shelf life. But nowadays plastics are known as carcinogenic, undegradable and unstable when exposed to heat. Therefore, alternative materials are needed which safer for the products and the consumers. One of the alternatives is by using edible casing based on gelatin and the gelatin which is safer for consumption by any people is gelatin from chicken claws. This research was aimed to create formulas of edible casing based on the extraction of gelatin chicken claws and lumbu putih garlic as an antioxidant and antimicrobial agent to produce edible casing with good physical properties, prevent oxidation also reduce microbial growth. The experimental design of this research had 2 factors, plasticizer types (Glycerol, Sorbitol, Sucrose) and Garlic Concentration (2.5%, 5%, 10%). The result of this study shows that the best combination of the edible casing according to the Zeleny method was sorbitol as the plasticizer and 5% of garlic concentration. It produced 0.18 mm of thickness, 17.7% of moisture content, 91.43% of elongation, 0.020 kgf/cm² of tensile strength, 1048.5 ppm of IC50, 85.348 cfu/ml of TPC value for three days of storage.